Venetoclax plus R- or G-CHOP in non-Hodgkin lymphoma: results from the CAVALLI phase 1b trial - Zelenetz, Andrew D. (Blood, 2019)
Novel strategies, such as chemosensitization with targeted agents, that build on the success of standard immunochemotherapy show promise for the treatment of non-Hodgkin lymphoma (NHL). Here, we report a phase 1b study investigating dose escalation of the BCL2 inhibitor, venetoclax, in combination with rituximab or obinutuzumab and cyclophosphamide, doxorubicin, vincristine, and prednisone (R-/G-CHOP) chemotherapy in B-cell NHL. Objectives included safety assessment and determination of a recommended phase 2 dose (RP2D). Fifty-six patients were enrolled, most with follicular lymphoma (43%) or diffuse large B-cell lymphoma (DLBCL; 32%). Dose-limiting toxicities were reported in 3/14 patients at the first venetoclax dose (200 mg/d), after which dosing was changed from daily to 10 days per cycle and escalated to 800 mg. A further reduction to 5 days per cycle occurred at the 800-mg dose level in the G-CHOP arm. Cytopenias were predominant among grade 3/4 events and reported at a higher rate than expected, particularly in the G-CHOP arm; however, safety was manageable. Overall response rates were 87.5% (R-CHOP and G-CHOP combinations); complete response (CR) rates were 79.2% and 78.1%, respectively. Most double-expressor (BCL2(+) and MYC(+)) DLBCL patients (87.5%; n = 7/8) achieved CR. Although the maximum tolerated dose was not reached, the RP2D for venetoclax with R-CHOP was established at 800 mg days 4 to 10 of cycle 1 and days 1 to 10 of cycles 2 to 8; higher doses were not explored, and this dosing schedule demonstrated an acceptable safety profile. This regimen is subsequently being evaluated in first-line DLBCL in the phase 2 portion of the study. This trial was registered at www.clinicaltrials.gov as #NCT02055820.